Implementation of Halal Certification through a-Self Declare Scheme in Micro and Small Enterprises: An Empirical Study in the Bandung City - Shasa, Shasa; Susilawati, Cucu; Herdiana, Dian (Pusat Kajian Halal Undip, 2025)
The study aims to find out the application of Government Regulation No. 39 of 2021 in the implementation of halal certification through a self-declaration scheme by MSEs in the city of Bandung. This research is in line with the requirement of halal certification for food and beverage products, including for Micro and Small Enterprises, in October 2026. This research also uses the Halal Product Assurance Law, sharia maqashid theory, and sharia principles in the implementation of halal certification with a self-declare scheme. This study adopts an empirical juridical approach, focusing on both the review of prevailing legal provisions and their practical application in the field. The research employs a descriptive-analytical method with the objective of presenting facts in a structured manner and interpreting them within the framework of Sharia economic law. The data utilized are qualitative in nature, gathered through several techniques such as conversations with stakeholders involved in the matter, analysis of official documentation, and literature reviews that strengthen the theoretical basis of this research. The findings indicate that the application of halal certification through the self-declaration scheme by MSEs in Bandung City aligns with the stipulations of Government Regulation No. 39 of 2021 on the Implementation of Halal Product Assurance. However, several obstacles were identified, particularly the lack of a Business Identification Number (NIB) among most MSEs and the challenges they face in accessing the SIHALAL system. However, even though there are inhibiting factors, the presence of Halal Companions is very helpful for MSEs in carrying out halal certification through self-declaration. The most important supporting factor in the implementation of halal certification through the self-declare scheme is the awareness of MSE actors of the importance of halal certification. Thus, the implementation of halal certification through the self-declare scheme is in accordance with maqāṣid al-syarī'ah, namely the basic goals that Islamic sharia wants to achieve in safeguarding human welfare. The principle of maslahah in the context of implementing halal certification through self-declaration is not just a legal justification, but is the main spirit of the policy. The self-declare scheme is also a form of moral and spiritual education for business actors, who are not only smart in business but also have high integrity and religious awareness. In addition, the self-declaration scheme also fulfils the written principle, because it can create transparency and provide legal certainty for both business actors and Muslim consumers.